Pendampingan Pembaruan Packaging dan Optimalisasi Branding UMKM Masyarakat di Kelurahan Kepatihan, Kecamatan Kaliwates, Kabupaten Jember - Ajeng Khusnul Samudra Pertiwi; Moh Khoiril Mustofa; Nida Kamila Hanifah Bastian; Cahyaningtyas Tetta Riandy; Novia Nur Chasanah; Putri Aulia Nadiyatul Jannah; Grace Winata; Daud Angga Yudha; Adam Naufalianto; Shavira Yuansa; Afifah Balqis Iftinan; Agung Rhaka Oktavianto; Hesti Ayu Verawati; Laili Rohmah Romadhoni; Sefi Ika Candra; Nurshadrina Kartika Sari (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Collaborative KKN is a service activity by students consisting of several universities. Our KKN location is in Kepatihan Village, Kaliwates District, Jember Regency. The main work program carried out by KKN Collaboration 229 students is to help Kepatihan Village MSMEs in the field of packaging and branding. Through the PANACOTTA work program, the KKN 229 group carries the theme of entrepreneurial development, entitled "Packaging Update and Branding Optimization". The purpose of this research is to find out strategies and help Kepatihan MSME players in optimizing packaging and branding. The method used in this research is a qualitative method with a descriptive type. The data analysis process is carried out with workshops/socialization and assistance from the data that has been obtained. The results of this research show that the Kepatihan community's MSMEs can increase community productivity, which is largely purely handmade. Collaborative KKN 229 students help and assist the community to optimize packaging and branding. For example, making logos, stickers, videos, banners, and social media. In terms of marketing, many of the communities sell their products door to door.